Step
*
1
1
1
2
1
1
of Lemma
generic-non-empty
1. T : Type
2. X : T
3. R : ℕ ⟶ (T List) ⟶ ℙ
4. p : i:ℕ ⟶ s:(T List) ⟶ (∃s':T List. (s ≤ s' ∧ (R i s')))
5. s : ℕ ⟶ (T List)
6. ∀i:ℕ. (R i (s i))
7. ∀i:ℕ. s i ≤ s (i + 1)
8. ∀i:ℕ. i < ||s i||
9. i : ℕ
10. R i (s i)
11. n : ℕ||s i||
⊢ s i[n] = s n[n] ∈ T
BY
{ Assert ⌜∀j,i:ℕ.  ((i ≤ j) 
⇒ s i ≤ s j)⌝⋅ }
1
.....assertion..... 
1. T : Type
2. X : T
3. R : ℕ ⟶ (T List) ⟶ ℙ
4. p : i:ℕ ⟶ s:(T List) ⟶ (∃s':T List. (s ≤ s' ∧ (R i s')))
5. s : ℕ ⟶ (T List)
6. ∀i:ℕ. (R i (s i))
7. ∀i:ℕ. s i ≤ s (i + 1)
8. ∀i:ℕ. i < ||s i||
9. i : ℕ
10. R i (s i)
11. n : ℕ||s i||
⊢ ∀j,i:ℕ.  ((i ≤ j) 
⇒ s i ≤ s j)
2
1. T : Type
2. X : T
3. R : ℕ ⟶ (T List) ⟶ ℙ
4. p : i:ℕ ⟶ s:(T List) ⟶ (∃s':T List. (s ≤ s' ∧ (R i s')))
5. s : ℕ ⟶ (T List)
6. ∀i:ℕ. (R i (s i))
7. ∀i:ℕ. s i ≤ s (i + 1)
8. ∀i:ℕ. i < ||s i||
9. i : ℕ
10. R i (s i)
11. n : ℕ||s i||
12. ∀j,i:ℕ.  ((i ≤ j) 
⇒ s i ≤ s j)
⊢ s i[n] = s n[n] ∈ T
Latex:
Latex:
1.  T  :  Type
2.  X  :  T
3.  R  :  \mBbbN{}  {}\mrightarrow{}  (T  List)  {}\mrightarrow{}  \mBbbP{}
4.  p  :  i:\mBbbN{}  {}\mrightarrow{}  s:(T  List)  {}\mrightarrow{}  (\mexists{}s':T  List.  (s  \mleq{}  s'  \mwedge{}  (R  i  s')))
5.  s  :  \mBbbN{}  {}\mrightarrow{}  (T  List)
6.  \mforall{}i:\mBbbN{}.  (R  i  (s  i))
7.  \mforall{}i:\mBbbN{}.  s  i  \mleq{}  s  (i  +  1)
8.  \mforall{}i:\mBbbN{}.  i  <  ||s  i||
9.  i  :  \mBbbN{}
10.  R  i  (s  i)
11.  n  :  \mBbbN{}||s  i||
\mvdash{}  s  i[n]  =  s  n[n]
By
Latex:
Assert  \mkleeneopen{}\mforall{}j,i:\mBbbN{}.    ((i  \mleq{}  j)  {}\mRightarrow{}  s  i  \mleq{}  s  j)\mkleeneclose{}\mcdot{}
Home
Index